THE EFFECT OF SOCIAL MEDIA MARKETING ON PURCHASE INTENTION IN IMPROVING TOURISM SECTOR IN BATAM - Edy Yulianto Putra; Leonardo Aprilson (LPPM Press STIE Indragiri Rengat, 2022)
This study aims to analyze the effect of social media marketing on purchase intention, as well as the relationship with brand awareness, brand image, and e-wom in the Batam City hospitality industry. The dependent variable in this study is purchase intention. The independent variables consist of social media marketing, brand image, e-wom and brand awareness. The sampling technique used in this research is purposive sampling. There are 2 types of data used in this study, namely primary data which is data received by researchers through the distribution of questionnaires to be processed. While secondary data is data collected through research articles, scientific journals, and others to meet research needs. The results showed that social media marketing variables had a significant positive effect on purchase intention, brand awareness, brand image and e-wom. The variables of e-wom, brand awareness, brand image, and social media marketing have a significant positive effect on purchase intention. Social media marketing variables have a significant positive effect on purchase intention through mediation of brand image, brand awareness and e-wom.